Local SIP Overload Control: Controller Design and Optimization by Extremum Seeking - Luca De Cicco; Giuseppe Cofano; Saverio Mascolo (IEEE Transactions on Control of Network Systems, 2015)
The session initiation protocol (SIP) is a signaling protocol for managing various types of real-time sessions between parties over an Internet Protocol (IP) network. An open issue is the control of overload situations that occur when the incoming flow of requests to a SIP server overcomes the server processing capacity. In particular, call establishment times increase due to overload, which triggers retransmissions and causes a further increase of the total incoming flow of requests. This paper proposes an overload control system for regulating both the queue length and the CPU load of the SIP server. The proposed control system is made of two proportional-integral controllers tuned by minimizing a proper cost function using the Extremum Seeking algorithm. A real working implementation of the SIP overload controller has been made in the open-source SIP server Kamailio. A performance evaluation and comparison of the proposed controller with the main proposals existing in the literature have been carried out. The results show that the proposed control system counteracts overload situations and provides a goodput close to the optimal while maintaining low call establishment delays and retransmission ratios.
Keywords: Servers; Control systems; Protocols; Algorithm design and analysis; Heuristic algorithms; Load modeling; Clustering algorithms; Extremum seeking; SIP overload control; SIP overload; SIP